IMPLEMENTASI KEGIATAN REDD+ PADA KAWASAN KONSERVASI DI INDONESIA - Ari Wibowo (Jurnal Analisis Kebijakan Kehutanan, 2016)
Reducing Emissions from Deforestation and Degradation Plus (REDD+) is a mechanism that is being established at the global level as a climate change mitigation mechanism in forestry sector. The study was conducted by collecting information related to the policies and regulations on the implementation ofREDD+ activities at the national level, methodological aspects at the global level and lessons learned from the implementation ofDemonstration Activities REDD in the conservation areas. The results showed that the Government had issued various regulations and technical guidances related to REDD+, including activities in the conservation area. However, in line with current developments, these regulations need to be updated or revised. The REDD+ implementation methodology was provided based on the IPCC guidelines, and not specific for the conservation area. Implementation ofREDD+ activities in the conservation areas, in addition to reduce emissions but also a chance to gain incentive, could also support forest sustainability, biodiversity and improve people's welfare. Nevertheless, some obstacles was also encountered in the implementation of REDD+. Therefore, strategies for the future are very necessary, so that REDD+ could be implemented and could achieve its objectives, without being fully dependent on the development ofnegotiations at the global level.